1986
DOI: 10.1002/j.1939-4640.1986.tb00890.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Neonatal Estrogen Administration on Rat Testis Development with Particular Reference to Sertoli Cells

Abstract: An ultrastructural and morphometric study of the testes in 15-, 22-, 45-, and 90-day-old neonatally estrogenized rats was performed. At 45 days of age, the Sertoli cells appeared immature in estrogenized rats, whereas they were fully mature in the controls. This finding might be related to a deficiency in gonadotropins and androgens during the postnatal period. In 90-day-old estrogenized rats, however, Sertoli cell maturation had occurred, which might be attributed to a recovery of hormone levels. Cytoplasmic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
1

Year Published

1987
1987
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 25 publications
3
22
1
Order By: Relevance
“…In the present study, degenerating Sertoli cells were only occasionally found in control or oestrogen-treated rats, although a great number of degenerating germ cells was found in neonatally oestrogenized rats (Gaytan et al, 1986 (Griswold et al, 1977) and in prepubertal rats after antiandrogen treatment with flutamide (Viguier-Martinez et al, 1983). The factors regulating postnatal Sertoli cell replication remain unclear, and the contribution of the postnatal cell divisions to the adult Sertoli cell population is not well established.…”
Section: Discussioncontrasting
confidence: 61%
See 3 more Smart Citations
“…In the present study, degenerating Sertoli cells were only occasionally found in control or oestrogen-treated rats, although a great number of degenerating germ cells was found in neonatally oestrogenized rats (Gaytan et al, 1986 (Griswold et al, 1977) and in prepubertal rats after antiandrogen treatment with flutamide (Viguier-Martinez et al, 1983). The factors regulating postnatal Sertoli cell replication remain unclear, and the contribution of the postnatal cell divisions to the adult Sertoli cell population is not well established.…”
Section: Discussioncontrasting
confidence: 61%
“…Since important hormonal alterations are present in neonatally oestrogen-treated rats during the early postnatal period (Bellido et al, 1985), it is tempting to suggest that the postnatal Sertoli cell divisions are not dependent on hormonal levels, and the finding that the replication pattern of Sertoli cells was retained in organ cultures in the absence of extragonadal factors (Steinberger & Steinberger, 1971) supports this view. However, the smaller tubular volume present in oestrogen-treated rats (Gaytan et al, 1986) results in the relative numbers of Sertoli cells being greater in oestrogen-treated rats than in control ones. The pseudostratified distribution of Sertoli cell nuclei in the former seems to reflect not only a lack of cell maturation but an effect of the reduced tubular volume.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Diethylstilbestrol (DES), a synthetic non-steroidal estrogen, exhibits a high estrogenic activity by binding to the ERs, and is thus a useful model compound for evaluating the potential toxicity of a wide range of chemicals that affect or mimic estrogen activity [7]. Previous studies have shown that fetal and/or neonatal treatment of rodents with DES induces adverse changes similar to those that occur after administration of estradiol-17尾 [1,10,34], dichlorodiphenyl trichloroethane (DDT) and methoxychlor (an estrogenic pesticide currently used as a substitute for DDT) [14,38]. It is suggested that many of the adverse changes to the testis and reproductive tract induced by exposure to estrogens result from a combination of high estrogen and low andro-gen activity [39].…”
mentioning
confidence: 99%